Parents’ and teachers’ attitude to family planning of adolescents with mild intellectual disabilities in the context of conceptions of gender and sexuality - Povilaitienė, Neringa; Radzevičienė, Liuda (Social Welfare: Interdisciplinary Approach, 2013)
There are quite many discussions in society on the issues of disabled people’s socialisation and integration. However, formation of disabled pupils’ gender identity, their gender, sexuality and family planning has not been suffi ciently analysed. The article aims to fi nd out how participants of the educational process (parents and teachers of adolescents with mild intellectual disabilities) treat conceptions of “gender” and “sexuality” and aspects of the dominating attitude to family planning and fertility of pupils with mild intellectual disabilities. It was found out in the research that a considerable share of parents/foster parents did not speak with their children about the future family, and many teachers expressed their negative attitude towards family planning of pupils with mild intellectual disabilities. However, there is also a different dominating opinion about family planning of these pupils in the context of sexuality and gender conceptions. Teachers note that these pupils must receive support in the formation of family relationships, while parents/foster parents seek to render aspects of a successful marriage.